LEGAL PROTECTION FOR KENJERAN BEACH FISHERMEN IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Bambang S. Irianto (EQUALEGUM International Law Journal, 2023)
Background. The reduction in the number of fishermen over the last 3-5 years has affected the fish catch in Surabaya, for the last 5 years it has continuously decreased. The uncertainty of the income obtained by fishermen from fishing and the limited fishing gear and the current increase in fuel prices add to the heavy burden on fishermen. In addition, the influence of the west wind season. The purpose of this research was to create a problem-solving strategy and develop community skills on the Kenjeran coastline both in the management of fish, and catch of the sea around the Kenjeran coastline. Research Method. This research was a type of Community Based Research. The research was conducted from March to June 2021, location was in Nambangan- Cumpat Fishermen Village, Kedung Cowek, Bulak, Surabaya City. The population in this study were members of the Fishermen's Group from each village, totaling 115 people. The research analysis approach is through Islamic eco-theology. Findings. Fishing activity is the main livelihood of coastal communities so when they cannot go to sea it means they cannot fulfill their daily needs. The results of this activity found several descriptions, situations of social structure, conditions, and problems faced by fishing communities, including population density, sanitation, slum environments, natural weather which is also an obstacle for fishermen to catch fish, narrow employment opportunities, and other social inequality. Conclusion. Efforts to understand Islamic eco-theology in the Kenjeran coastal fishing community are one of the means to conserve the coastal environment.